A-Site Ion Doping in Cs2AgBiBr6 Double Perovskite Films for Improved Optical and Photodetector Performance - Yuejia Wu; Yanpeng Meng; Qirun Hu; Songchao Shen; Chengxi Zhang; Ang Bian; Jun Dai (Crystals)
Perovskite materials, as emerging semiconductors, have attracted significant attention for their exceptional optoelectronic properties, tunable bandgaps, ease of fabrication, and cost-effectiveness, making them promising candidates for next-generation optoelectronic devices. The all-inorganic perovskite Cs2AgBiBr6 distinguishes itself from other perovskite materials due to its remarkable optical absorption and emission properties, excellent stability, prolonged carrier recombination lifetime, and nontoxic characteristics. However, a deeper understanding of its unique luminescent properties and a further optimization of its structure and performance are still necessary. This study systematically investigates the optimization of Cs2AgBiBr6 double perovskite films through A-site Na+ doping. At an optimal Na+ doping concentration of 3.5% (Na0.07Cs1.93AgBiBr6), the film shows 1.4 times and 2.7 times enhancement in light absorption and photoluminescence intensity, compared to the undoped film. Low-temperature spectroscopy measurements indicate that Na0.07Cs1.93AgBiBr6 exhibits higher exciton binding energy and phonon energy. Based on Na0.07Cs1.93AgBiBr6, the photodetectors demonstrate significant performance improvements, with a high photocurrent response of 10−2 A, a photo-to-dark current ratio (PDCR) of 7.57 × 104, a responsivity (R) of 16.23 A/W, a detectivity (D*) of 2.92 × 1012 Jones, a linear dynamic range (LDR) of 98.75 dB, and a fast response time of 943 ms. This work provides a promising strategy for optimizing all-inorganic perovskite materials through doping and offers guidance for enhancing high-performance photodetectors.